Thrombospondin-1 Partly Mediates the Cartilage Protective Effect of Adipose-Derived Mesenchymal Stem Cells in Osteoarthritis - Maumus, Marie; Manferdini, Cristina; Toupet, Karine; Chuchana, Paul; Casteilla, Louis; Gachet, Mélanie; Jorgensen, Christian; Lisignoli, Gina; Noël, Danièle (Frontiers in Immunology, 2017)
Objective Assuming that mesenchymal stem cells (MSCs) respond to the osteoarthritic joint environment to exert a chondroprotective effect, we aimed at investigating the molecular response setup by MSCs after priming by osteoarthritic chondrocytes in cocultures. Methods We used primary human osteoarthritic chondrocytes and adipose stem cells (ASCs) in mono- and cocultures and performed a high-throughput secretome analysis. Among secreted proteins differentially induced in cocultures, we identified thrombospondin-1 (THBS1) as a potential candidate that could be involved in the chondroprotective effect of ASCs. Results Secretome analysis revealed significant induction of THBS1 in ASCs/chondrocytes cocultures at mRNA and protein levels. We showed that THBS1 was upregulated at late stages of MSC differentiation toward chondrocytes and that recombinant THBS1 (rTHBS1) exerted a prochondrogenic effect on MSC indicating a role of THBS1 during chondrogenesis. However, compared to control ASCs, siTHBS1-transfected ASCs did not decrease the expression of hypertrophic and inflammatory markers in osteoarthritic chondrocytes, suggesting that THBS1 was not involved in the reversion of osteoarthritic phenotype. Nevertheless, downregulation of THBS1 in ASCs reduced their immunosuppressive activity, which was consistent with the anti-inflammatory role of rTHBS1 on T lymphocytes. THBS1 function was then evaluated in the collagenase-induced OA model by comparing siTHBS1-transfected and control ASCs. The protective effect of ASCs evaluated by histological and histomorphological analysis of cartilage and bone was not seen with siTHBS1-transfected ASCs. Conclusion Our data suggest that THBS1 did not exert a direct protective effect on chondrocytes but might reduce inflammation, subsequently explaining the therapeutic effect of ASCs in OA.